Legal Protection of Instrument Witnesses in Maintaining the Secret Position Notary - Ira Nur Istiqomah; Rachmi Sulistyarini; Dhia Al Uyun (PT FORMOSA CENDEKIA GLOBAL, 2023)
Notary as an official who is legally authorized to make official deeds, in accordance with the provisions in Law Number 2 of 2014 concerning amendments to Law Number 30 of 2004 concerning the office of notary. A requirement that must be met to make an authentic deed is the presence of witnesses. This witness is a person who is present when an event occurs and has the ability to provide information that can prove that the event actually occurred. An instrument witness is a person who is present in the process of making a deed by a notary, where his name is also recorded in the deed. This study aims to analyze how the legal rules regulate and protect the confidentiality of information from instrument witnesses in maintaining the confidentiality of the notarial deed they witnessed. To protect them from possible undesirable consequences, there needs to be legal protection given to witnesses in the process of making notarial deeds. This is important because witnesses are often involved in problems or disputes that arise in relation to the documents they witness. In order for witnesses not to be victimized or further involved in the case, legal protection must be guaranteed to ensure that they will not be harmed due to their role as witnesses in the notarial deed. This research applies a normative legal research method using a statue approach. There are no clear provisions regarding the legal rules of instrument witnesses in notarial deeds based on research. The absence of regulations regarding witnesses contained in the Notary Position Law or other regulations. Law No. 31 of 2014 amending Law No. 13 of 2006 on Witness and Victim Protection serves to provide legal protection to witnesses involved in the process of making notarial deeds. However, in Law No. 31 of 2014 amending Law No. 13 of 2006 on Witness and Victim Protection, the protection of witnesses' rights is still inadequate. Witnesses who are given protection by the Law are individuals who are directly involved and have knowledge and experience of a criminal offense. Meanwhile, a notarial deed witness is a person who is present to witness the formal process of making a deed. The Law on the Protection of Witnesses and Victims is inadequate in providing legal protection to witnesses involved in the process of making notarial deeds